Factors Affecting English Communication Skills of Grade 11 Students at Bestlink College of the Philippines (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The English competency of the Philippines is considered to be one of the greatest assets that made Filipinos known and recognized to the global workforce, thereby attracting foreign investors that contribute to the growing economy of the country. English communication will always be the most useful skill of every educated Filipino because it is already embedded in our culture, history, and identity as a bilingual nation. However, a recent study states that the English competency of Filipinos declined in thepast years. The present research only involved 30 Grade 11 students. A descriptive method was used, and a questionnaire was given to gather data from the respondents consisting of the respondents’ profiles; the factors affecting English communication skills; and how the factors affect their daily conversational skills, written tasks, and public speaking skills. The majority of the respondents are female students aged 17 years old from the Humanities and Social Sciences Strand. The most significant factor was the medium of communication in which the practice of the language is observed daily. The preferred language of the respondents to use is Bilingual, thereby significantly affecting their fluency. Media influence the learners as they allot most of their time to social networking platforms, such as Facebook, where the proficiency of the English language is not given that much importance because people use slang and colloquial words nowadays. Students are uncomfortable speaking English because of MTB, where primary learners are taught by using their MT. Thus, students have difficulty in translating terms to English, which also leads to a lack of ideas for creative writing. Communication becomes effective when a communicator is competent and has a broad understanding of the language. English competency provides a better opportunity in the corporate world and other fields. Family should help promote language development at home by doing a habitual studying lesion guided by parents themselves. Curriculum developers should develop a curriculum that will meet the needs of diverse backgrounds and levels of English language learners and provide the most appropriate instructional material and approach for diverse learners so that they can cope up with the global competencies. A strong connection between teacher and student should be established to ease the learning process. Lastly, the use of social media should be maximized by creating an online platform that will serve as an extension of learning.
Keywords: MTB